2015
DOI: 10.54207/bsmps1000-2015-13u234
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical properties of Anthocephalus cadamba (Roxb.) Miq. at five different ages

Abstract: Anthocephalus cadamba is an important tree species for pulp and paper industry. Anatomical studies were conducted between trees of different age viz., 2, 4, 6, 8 and 10 were selected from different plantation. One plus tree from each age was felled for the study. The transverse discs of 10 cm thickness were collected from three different heights of tree representing base, middle and top positions. Anatomical properties like Fibre Length, Fibre Diameter, Fibre Lumen Width, Fibre Wall Thickness, Flexibility, Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…The results are similar to those reported by Kusumastuti (2018), who found that the average fiber length of 3-years-old ganitri was 1040 μm. However, research on woods which has a similar density such as benuang wood (Marbun et al 2019), 6 years-old jabon wood (Gujar et al 2015) and white jabon wood (Pertiwi et al 2018) have longer values of fiber length than that of ganitri wood, which is 1599.39 μm, 1781 μm, and 1520 μm, subsequently.…”
Section: Fiber Lengthmentioning
confidence: 99%
“…The results are similar to those reported by Kusumastuti (2018), who found that the average fiber length of 3-years-old ganitri was 1040 μm. However, research on woods which has a similar density such as benuang wood (Marbun et al 2019), 6 years-old jabon wood (Gujar et al 2015) and white jabon wood (Pertiwi et al 2018) have longer values of fiber length than that of ganitri wood, which is 1599.39 μm, 1781 μm, and 1520 μm, subsequently.…”
Section: Fiber Lengthmentioning
confidence: 99%